2013
DOI: 10.1002/jsfa.6439
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of nitrites and nitrates levels in leafy vegetables (spinach and lettuce): a contribution to risk assessment

Abstract: Considering the non-negligible percentage of 'not-compliant' samples for nitrates (6.0%), control is needed. Moreover, it is possible to suggest the introduction in the Communities Regulations of a 'maximum admissible level' for nitrites in leafy vegetables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 9 publications
3
46
0
7
Order By: Relevance
“…Absorption of nitrate occurs most often from natural sources, but vegetables accumulate a significant portion of nitrate from nitrogen-based fertilizers, which are used for fertilizing plants for faster and bigger growth (Shahid Umar, 2007). Leafy vegetables, such as lettuce or spinach, contain the highest concentrations of nitrate (Iammarino, 2014). Approximately 80% of dietary nitrates are derived from vegetable consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Absorption of nitrate occurs most often from natural sources, but vegetables accumulate a significant portion of nitrate from nitrogen-based fertilizers, which are used for fertilizing plants for faster and bigger growth (Shahid Umar, 2007). Leafy vegetables, such as lettuce or spinach, contain the highest concentrations of nitrate (Iammarino, 2014). Approximately 80% of dietary nitrates are derived from vegetable consumption.…”
Section: Introductionmentioning
confidence: 99%
“…The concentration of nitrate in organic cultures was lower [43]. The study of Iammarino et al (2014) Spinach is highly regarded by farmers and nutritionists due to its resistance to contamination rooting rapid growth and nativeness. Spinach nitrate contamination has been reported in most Iranian cities [18,35].…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted nitrite and nitrate of 150 leafy vegetables and their risk assessment showed that nitrate in spinach and lettuce is higher than the standard limit. Nitrite levels also varied from 28.5 to 19.5/19 [44]. Investigating studies on lettuce and eggplant in Iran, nitrate pollution of these products was not exceeded by standards [16, 30, 35-36, 38, 40].…”
Section: Resultsmentioning
confidence: 99%
“…Nitrite is an essential component of a healthy diet as it reacts with hemoglobin and produces methemoglobin which enables transporting of oxygen at the cellular level . However, excess levels of nitrite in the presence of amines or amides in the stomach convert to nitrosamines which have been reported to be carcinogenic and potentially harmful to humans . Therefore, it is important for environmental reasons to monitor nitrite levels as the World Health Organization (WHO) and the United States Environmental Protection Agency has set limits for the total nitrite content that is allowable in water as well as WHO and EU Scientific Committee for Food recommendations on the amount of nitrite used in foods ,…”
Section: Introductionmentioning
confidence: 99%
“…[36] However, excess levels of nitrite in the presence of amines or amides in the stomach convert to nitrosamines which have been reported to be carcinogenic and potentially harmful to humans. [37][38] Therefore, it is important for environmental reasons to monitor nitrite levels as the World Health Organization (WHO) and the United States Environmental Protection Agency has set limits for the total nitrite content that is allowable in water as well as WHO and EU Scientific Committee for Food recommendations on the amount of nitrite used in foods. [32,39] In this work, we investigate the influence of the in situ upd of lead and copper on the electrodeposition of nanostructured gold from gold bromide and chloride salts and investigate the influence that the structure of the deposit has on the electrochemical detection of nitrite.…”
Section: Introductionmentioning
confidence: 99%